Constraint Clustering for Promotion Application: Central Java Case Study - Maulindar, Joni; Awang Long, Zalizah; Che Mustapha, Jawahir; Purnomo, Singgih (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Organizations utilize Talent Management to enhance competitiveness, improve employee quality, develop potential, and retain talent. Talent management also plays a crucial role in the career development of lecturers. Promotions in the academic ranks and positions of lecturers in Indonesia are essential to consider, as they significantly impact the quality of lecturers, the accreditation value of higher education, and the global rankings of universities. In this study, a questionnaire was administered to 406 respondents. The results revealed six clusters correlated with the challenges of applying for functional lecturer positions. Based on the cluster analysis, Cluster 0 (20%) exhibited minimal obstacles, Cluster 1 (27%) faced highly challenging obstacles, Cluster 2 (13%) experienced neutral obstacles, Cluster 3 (15%) encountered manageable obstacles, Cluster 4 (18%) dealt with easily surmountable constraints, and Cluster 5 (7%) experienced significant hurdles. Future research could explore implementing a new talent management model, particularly for lecturers who need help applying for functional positions.